2015
DOI: 10.1103/physreve.91.053023
|View full text |Cite|
|
Sign up to set email alerts
|

Role of inertia for the rotation of a nearly spherical particle in a general linear flow

Abstract: We analyse the angular dynamics of a neutrally buoyant nearly spherical particle immersed in a steady general linear flow. The hydrodynamic torque acting on the particle is obtained by means of a reciprocal theorem, regular perturbation theory exploiting the small eccentricity of the nearly spherical particle, and assuming that inertial effects are small, but finite.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 12 publications
3
22
0
Order By: Relevance
“…22 The results of this calculation agree to order ϵ with the results presented above. Further, we have checked that the particle-inertia correction in Eq.…”
Section: B Linear Stability Analysis At Infinitesimal Re Ssupporting
confidence: 80%
“…22 The results of this calculation agree to order ϵ with the results presented above. Further, we have checked that the particle-inertia correction in Eq.…”
Section: B Linear Stability Analysis At Infinitesimal Re Ssupporting
confidence: 80%
“…Influence of the body inertia in the case where the particle stands close to a wall also induces dramatic changes because, combined with the wall-particle hydrodynamic interaction, it induces a drift of the particle towards the wall (Gavze & Shapiro 1998). Small-but-finite fluid inertia effects are known to affect the hydrodynamic torque and angular motion in such a way that the marginal stability of the Jeffery orbits of spheroidal particles is broken (Subramanian & Koch 2005;Einarsson et al 2015a;Candelier et al 2015;Rosen et al 2015;Dabade et al 2016); these conclusions were recently extended to an arbitrary linear flow field (Marath & Subramanian 2018). Unsteady fluid inertia effects have also been shown to make a significant contribution to the body-shape dependence of the stability exponents of the Jeffery orbits (Einarsson et al 2015b).…”
Section: Influence Of Small Inertia Effects On the Sedimentation Of Nmentioning
confidence: 99%
“…Ding and Aidun [23] showed through direct numerical simulations that the period of a prolate spheroid diverges for higher Reynolds numbers as the particle remains motionless when it is nearly aligned with the flow direction. Recently, Einarsson et al [24][25][26][27][28][29] have shown theoretically that in the limit of weak flow and particle inertia, the degeneracy of Jeffery orbits is indeed lifted. The first effects due to weak inertia cause a prolate spheroid in simple shear to drift to a stable tumbling limit cycle, whatever the initial condition [24].…”
Section: Introductionmentioning
confidence: 99%